Antigenic drift as a mechanism for tumor evasion of destruction by cytolytic T lymphocytes - Bai, Xue-Feng; Liu, Jinqing; Li, Ou; Zheng, Pan; Liu, Yang (The Journal of Clinical Investigation, 2003)
It is established that mutations in viral antigenic epitopes, or antigenic drifts, allow viruses to escape recognition by both Ab’s and T lymphocytes. It is unclear, however, whether tumor cells can escape immune recognition via antigenic drift. Here we show that adoptive therapy with both monoclonal and polyclonal transgenic CTLs, specific for a natural tumor antigen, P1A, selects for multiple mutations in the P1A antigenic epitope. These mutations severely diminish T cell recognition of the tumor antigen by a variety of mechanisms, including modulation of MHC:peptide interaction and TCR binding to MHC:peptide complex. These results provide the first evidence for tumor evasion of T cell recognition by antigenic drift, and thus have important implications for the strategy of tumor immunotherapy.